Sol-gel auto-combustion synthesis of cobalt ferrite and it's cytotoxicity properties - Kanagesan, Samikannu; Hashim, Mansor; Subramani, Tamilselvan; Mohammed Alitheen, Noorjahan Banu; Ismail, Ismayadi; Mustaffa, Muhammad Syazwan; Muhammad Zulkimi, Muhammad Misbah (National Institute R&D Materials Physics, 2013)
Cobalt ferrite (CoFe2O4) nanoparticles were successfully synthesized by a sol-gel combustion technique. The particle size as determined by a transmission electron microscope was about 25 nm. A maximum saturation magnetization of 22.31 emu/g and a coercivity of 118 Oe were achieved for the samples. The effect of CoFe2O4 nanoparticles on 4T1 murine breast cancer cells was explored by cytotoxicity assay and flow cytometer analysis. The lower concentrations of CoFe2O4 nanoparticles did not induce any toxicity in cells, when exposed for 24 h. Concentrations exceeding 400 μg/ml produced significant morphological changes and induced cell death by apoptosis and necrosis.